2017
DOI: 10.1007/s00216-017-0829-1
|View full text |Cite
|
Sign up to set email alerts
|

Counting the number of enzymes immobilized onto a nanoparticle-coated electrode

Abstract: To immobilize enzymes at the surface of a nanoparticle-based electrochemical sensor is a common method to construct biosensors for non-electroactive analytes. Studying the interactions between the enzymes and nanoparticle support is of great importance in optimizing the conditions for biosensor design. This can be achieved by using a combination of analytical methods to carefully characterize the enzyme nanoparticle coating at the sensor surface while studying the optimal conditions for enzyme immobilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…It has the lowest amount of enzyme with the largest footprint (after P-0), suggesting that the enzyme has an expanded conformation on this surface which we found to be highly negatively charged. Overall, these calculated footprints are generally larger than the theoretical footprint of GOx predicted from its crystal structure (21, 67, or 195 nm 2 ) ,, but are in line with other reported values on Au (between 528 and 823 nm 2 ) and Au nanoparticles (between 250 and 300 nm 2 ), suggesting that GOx flattens out to some degree during adsorption. , Note that the native GOx dimensions are those of a deglycosylated GOx molecule, thus implying a larger structure for the protein in solution . We also stress the qualitative aspect of these calculations due to our assumptions.…”
Section: Resultssupporting
confidence: 88%
“…It has the lowest amount of enzyme with the largest footprint (after P-0), suggesting that the enzyme has an expanded conformation on this surface which we found to be highly negatively charged. Overall, these calculated footprints are generally larger than the theoretical footprint of GOx predicted from its crystal structure (21, 67, or 195 nm 2 ) ,, but are in line with other reported values on Au (between 528 and 823 nm 2 ) and Au nanoparticles (between 250 and 300 nm 2 ), suggesting that GOx flattens out to some degree during adsorption. , Note that the native GOx dimensions are those of a deglycosylated GOx molecule, thus implying a larger structure for the protein in solution . We also stress the qualitative aspect of these calculations due to our assumptions.…”
Section: Resultssupporting
confidence: 88%
“…The opposite trend was observed for cytosolic phospholipase also adsorbed on vesicles . For NP based surfaces, it was demonstrated that the enzyme immobilization on a high curvature surface is beneficial to retain enzymatic activity by preventing denaturing and minimizing changes in the enzyme tertiary structure. Alternatively, in ref the activity of GOx on the gold flat surface was higher than that on NPs. The lack of consensus regarding the surface curvature influence on the enzyme catalytic activity is probably due to multiple factors influencing the activity, thus making it difficult to fully decouple the curvature factor.…”
Section: Results and Discussionmentioning
confidence: 98%
“…In comparison, the aggregation of NP40 is prevented for R / R th = 2, suggesting the adsorption of more than one layer of the enzyme. A consequent change of GOx conformation could occur on large NPs leading to a larger footprint of the enzyme on a flat surface [ 33 ] than on small NPs, with a high curvature [ 22 ]. Upon adsorption, the enzymes could also unfold leading to the formation of two layers.…”
Section: Resultsmentioning
confidence: 99%